2022
DOI: 10.7150/thno.67530
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in cryoablation cancer therapy and nanoparticles mediated cryoablation

Abstract: With rapid advances in modern imaging, minimally invasive ablative procedures have emerged as popular alternatives to surgical removal of tumors. Tumor ablation modalities currently offered in clinical practice include microwave ablation, radiofrequency ablation, cryoablation, high-intensity focused ultrasound, and irreversible electroporation. Cryoablation, a non-heat-based method of ablation, is increasingly being used for treating various solid tumors. Accumulated comparative data of cryoablation versus hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 231 publications
(219 reference statements)
0
37
0
Order By: Relevance
“…In addition to therapeutic employment, one of the prominent biomedical MNP applications is diagnostic imaging. [ 58–60 ] In MRI, a widely performed diagnostic test, the MNPs are used as a contrast agent to produce clearer images in which the spin–spin relaxation time ( T 2 ) of adjacent hydrogen atoms is quantified as an image. Clinically, patients are first injected with contrast agents that include the MNPs and then subjected to MRI.…”
Section: Multifunctional Mnpsmentioning
confidence: 99%
“…In addition to therapeutic employment, one of the prominent biomedical MNP applications is diagnostic imaging. [ 58–60 ] In MRI, a widely performed diagnostic test, the MNPs are used as a contrast agent to produce clearer images in which the spin–spin relaxation time ( T 2 ) of adjacent hydrogen atoms is quantified as an image. Clinically, patients are first injected with contrast agents that include the MNPs and then subjected to MRI.…”
Section: Multifunctional Mnpsmentioning
confidence: 99%
“…Previous studies reported that cell contents released by cryoablation contain "danger signals" such as pro-inflammatory cytokine, heat shock protein, DNA, and RNA recognized by toll-like receptors, which activate the natural immune response (1,3,4,7,(13)(14)(15). With the wide application of the new generation of immunotherapy represented by immune-checkpoint inhibitors, cryoablation combined with immunotherapy has shown more and more broad prospects, and several clinical trials are currently exploring combination therapies (16)(17)(18)(19)(20)(21)(22). However, the timing and sequence of cryoablation, the extent of cryoablation, and the choice of target tumor are still unclear, which requires further understanding of the mechanism of cryoablation enhancing anti-tumor immunity.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] However, one of the challenges of PTT is that the externally introduced heat may cause burns in the skin tissue. [ 7 ] The smaller the area being heated, the shorter the treatment time required, and hence, the fewer the adverse effects. Conversely, longer tumor treatment duration, or lower temperatures do not achieve therapeutic goals.…”
Section: Introductionmentioning
confidence: 99%